Interkoneksi Paradigma Pendidikan Islam di Sekolah Menengah Atas Tren Sains Tebuirang Jombang - Fahrudin Fahrudin; Sepma Pulthinka Nur Hanip (Belajea: Jurnal Pendidikan Islam, 2020)
This study aimed to analyze Islamic Education in high school Trens Science studying and researching verses of the universe are contained in the Qur'an and the Hadith serve as a reflection of the unity of the Divine principle. This is what later became basic principles in organizing education in the high school Trensain-based monotheism. Through research field research this researchers using a qualitative approach-descriptive methods of data collection used observation, interview, and documentation. The theoretical framework to analyze the findings of the field used the concept of Islamization of Science Ismail Raji Al-Faruqi. The results of the findings in the field show that, high school Trens Science Tebuireng, applying the paradigm of Islamic education based on Science which is based on Al-qur'an dah Hadith as a system of education that is in harmony with the idea of the islamization of Science Ismail Raji Al-Faruqi